2017
DOI: 10.1515/gej-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remittances on Economic Growth in Developing Countries: The Role of Openness

Abstract: The paper examines the empirical relationship between remittances and economic growth for a sample of 62 developing countries over the time period 1990–2014. Remittances seem to promote growth only in the ‘more open’ countries. That is because remittances are in themselves not sufficient for growth. The extent of the benefit depends on domestic institutions and macroeconomic environment in the receiving country. Unlike the ‘less open’ countries, ‘more open’ countries have better institutions and better financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…An increase in remittance flows of 1% of GDP could have led to significant economic growth per capita in the 1990s. These results may be connected with the role of openness as noted by Reference [50] highlighting the link between the openness and better institutions. The negative influence after 2000 was possibly caused by the overall economic slowdown that started in 2008 and resulted into the lower remittance flows to the developing countries.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…An increase in remittance flows of 1% of GDP could have led to significant economic growth per capita in the 1990s. These results may be connected with the role of openness as noted by Reference [50] highlighting the link between the openness and better institutions. The negative influence after 2000 was possibly caused by the overall economic slowdown that started in 2008 and resulted into the lower remittance flows to the developing countries.…”
Section: Resultsmentioning
confidence: 53%
“…Our estimates revealed that an increase in development aid and remittance flows led to significant long-term economic growth per capita only in the 1990s. These results may be connected with the role of openness as noted by Reference [50] highlighting the link between the openness and better institutions. A two-way effect may be present.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This belief is somewhat justified because remittances in developing countries are found positively related with household welfare but at the same time produce more volatile business cycles [7,12,15]. Yet, whether remittances have any role in economic growth or financial development remains a country-specific question [3,8,9].…”
Section: Introductionmentioning
confidence: 99%